2016
DOI: 10.1002/aenm.201601803
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated CdS Buffer Layers Enabling High Open‐Circuit Voltages in Earth‐Abundant Cu2BaSnS4 Thin‐Film Solar Cells

Abstract: Earth‐abundant Cu2BaSnS4 (CBTS) thin films exhibit a wide bandgap of 2.04–2.07 eV, a high absorption coefficient > 104 cm−1, and a p‐type conductivity, suitable as a top‐cell absorber in tandem solar cell devices. In this work, sputtered oxygenated CdS (CdS:O) buffer layers are demonstrated to create a good p–n diode with CBTS and enable high open‐circuit voltages of 0.9–1.1 V by minimizing interface recombination. The best power conversion efficiency of 2.03% is reached under AM 1.5G illumination based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
123
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 54 publications
10
123
0
1
Order By: Relevance
“…Thus, the energy level diagrams (Figure d) show that for oxygen plasma‐treated CdS, the CBM is upshifted, which means that the Fermi level is farther from the CBM. This increased distance can prevent the electrons from reaching the Fermi level, which reduces the effective interface recombination between the Sb 2 Se 3 and CdS . On the other hand, with the decrease in the surface roughness of the oxygen plasma‐treated CdS film, the Sb 2 Se 3 film can grow more uniformly and unidirectionally on CdS film; therefore, the contact between the CdS and Sb 2 Se 3 is improved, which will decrease the contact resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the energy level diagrams (Figure d) show that for oxygen plasma‐treated CdS, the CBM is upshifted, which means that the Fermi level is farther from the CBM. This increased distance can prevent the electrons from reaching the Fermi level, which reduces the effective interface recombination between the Sb 2 Se 3 and CdS . On the other hand, with the decrease in the surface roughness of the oxygen plasma‐treated CdS film, the Sb 2 Se 3 film can grow more uniformly and unidirectionally on CdS film; therefore, the contact between the CdS and Sb 2 Se 3 is improved, which will decrease the contact resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been experimentally shown that CBTSSe/FTO and CZTS/ITO interfaces are practically realizable. [19,20] Therefore, our proposed triple junction solar cell is experimentally viable with the existing fabrication technology.…”
mentioning
confidence: 96%
“…As a result, current density falls significantly with the higher thickness of CZTS (Figure 2(a)) because of the reduced optical power absorption in the bottom cell. Thus, higher thickness of [19] 7 [18] 8.5 [17] 7 [16] Band gap (eV) 1.9 [14] 1.45 [18] 0.97 [17] 0.9 [16] Electron affinity (eV) 3.6 [19] 4.1 [24] 4.05 [17,25] 4.05 [13] Electron effective mass (m e /m o ) 0.37 [14,15] 0.18 [13,16] 0.08 [17] 0.07 [13,16] Hole effective mass (m p /m o ) 1.68 [14] 2 [13,16] 0.3 [17] 0.2 [13,16] Electron mobility (cm 2 V À1 s À1 ) 3 0 [26] 40 [21,24] 75 [23] 145 [13,21] Hole mobility (cm 2 V À1 s À1 ) 1 0 [27] 25 [21] 1 [17,23] 35 [13,21] Acceptor concentration (cm…”
mentioning
confidence: 99%
See 2 more Smart Citations